Influencing the international forest policy: the role of collaborative research - Bose, P. (2003)
‘Does research in collaboration with partners has any impact on shaping global forest policy?’ is a question being asked more frequently. Often, the challenges faced by most academic research institutions while working with partners and trying to measure impacts are in terms of: a. Interpreting impact of research partnership, which is difficult by the fact that different stakeholders understand ‘impact’ differently. b. Implementation hindrance in working with ‘partners’. This paper will deal with the above-mentioned challenges, addressing the following questions related to partnerships in adaptive collaborative management plans: a. What role is there for research? b. What is needed to facilitate the learning perspective in terms of the institutional environment, leadership and organisational change? c. What is the potential of research to contribute to improved livelihoods and sustainable forest management? For the Center for International Forestry Research (CIFOR), doing research in collaboration with partners remains the key success mantra in influencing major global policy issues – forests and people – and public opinion. The purpose of this paper is to present CIFOR’s decade-long learning experience, process and strategy of working in close alliance with its partners. The paper begins by exploring CIFOR’s strategic relationship in doing science with local communities, civil societies, academic and research institutes, governments, donors and policy makers. Then, it goes on to sketch out how networking, capacity building, bridging valuable links and acting as an intermediary among partners intersecting the global, national and local levels have impact on forest policy. Briefly, it illustrates how international institutes such as the World Bank, FAO, GEF/CBD, WRI, UNFF and ITTO, among other organisations, are utilising CIFOR’s research and network studies in prioritising and disseminating through their policy documents. These major institutes often provide support such as technical advice as well as financial investment in forest activities to governments, NGOs and academics. In third part, the paper addresses CIFOR and its partner’s achievements in assisting institutions and individuals from developing countries through its collaborative research approach. The study corroborates other findings that ‘partnership’ research on forests and people is successful thanks to strong, strategic, shared leadership that purposely seeks creating collaborative advantage. Also, that collaborative research has higher mutual accountability and shared vision with sense of purpose. Primarily findings suggest that collaboration research yields greater utility value through the dissemination and implementation of research outputs. The study concludes that: a. partnership can be best understood as a social instrument that can enhance policy effectiveness; b. though collaborative research is a slow process, it can influence major decision through its findings; c. collaborative research plays a crucial role in establishing networks and thereby wider dissemination. Finally, we conclude that, while the impact of research on policies changes over a period of time, one thing that remains constant is the value of partnership.